Grammatical cohesion found in undergraduate student’s thesis writing: A case study at one private university in Indonesia - Ulfa, Risma Liyana; Ramadhani, Reski (English Learning Innovation, 2024)
Writing an excellent and comprehensive text depends on applying appropriate grammatical cohesive devices. This study aims to investigate the types and errors of the grammatical cohesive devices found in the undergraduate student's thesis. The analysis used in the present study applied the framework of Systemic Functional Linguistics (SFL) proposed by Halliday and Hasan (2014). Through the qualitative design with content analysis, this study examines two undergraduate students' theses, focusing on finding and discussing sections at one private university in Jakarta. The analysis revealed that grammatical cohesive devices in the thesis are not diverse. The data's most dominant grammatical cohesive devices are references and conjunctions—no elliptical and substitution devices are found in the data. Besides, errors in applying grammatical cohesion in the undergraduate students' writing were found, especially in using personal and demonstrative references and extension conjunctions. It indicates that the students still lack understanding in applying the knowledge of grammatical cohesion in their writing, influencing the readers' understanding in capturing information from the thesis. It implies that the knowledge of appropriate grammatical cohesion is essential for students in academic writing, predominantly undergraduate thesis, to convey the ideas and information properly and coherently.